2011
DOI: 10.1007/s12665-011-1065-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of fluoride concentration in groundwaters of Shivani watershed area, Karnataka state, South India, through geospatial information system

Abstract: Hydrogeochemical investigations with emphasis on groundwater fluoride concentrations were carried out in the Shivani watershed area, Karnataka, South India. This drought-prone watershed is characterised by poor groundwater potential and is composed of different lithounits like gneisses, migmatites, tonalites, mafics-ultramafics, conglomerates and quartzites. Analysis of spatial variation of groundwater fluoride concentration through the use of GIS technology software platforms like ArcView 3.2a and MapInfo Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The present study also found that water sampled from the districts of Kolar, Bellary and Koppal contained higher fluoride concentrations than those of the other districts investigated, an observation similar to that found in previous studies. [22][23][24] Although districts such as Bijapur, Belgaum, Dharwad and Haveri have lower water fluoride levels than the permissible limit, previous investigations conducted 25,26 found that these values were higher than those determined here. In contrast, mean fluoride concentrations in the districts of South Kannada (0.63 ppm) and Mysore (0.75 ppm) are lower than the recommended lower limit, the former strikingly so.…”
Section: Discussionmentioning
confidence: 70%
“…The present study also found that water sampled from the districts of Kolar, Bellary and Koppal contained higher fluoride concentrations than those of the other districts investigated, an observation similar to that found in previous studies. [22][23][24] Although districts such as Bijapur, Belgaum, Dharwad and Haveri have lower water fluoride levels than the permissible limit, previous investigations conducted 25,26 found that these values were higher than those determined here. In contrast, mean fluoride concentrations in the districts of South Kannada (0.63 ppm) and Mysore (0.75 ppm) are lower than the recommended lower limit, the former strikingly so.…”
Section: Discussionmentioning
confidence: 70%
“…(2009),Salve et al (2008),Singh et al (2011),Vikas et al (2009),Rao (2009),Kantharaja et al (2012),Guo et al (2012),Gupta et al (1999),Madhnure et al et al (1993),Rao et al (1993),Chakraborti et al (2000),Kundu et al (2001), Farooqi et al (2007a), Brindha et al (2011), Dar et al (2011), Kim et al (2011), Singh et al (2011), Jabal et al (2014) -Calcium Chakraborti et al (2000), Rao (2009) Jacks et al (1993), Gupta et al (1999), Das et al (2003), Vasquez et al (2006), Ramanaiah et al (2006), Farooqi et al (2007a), Madhnure et al (2007), Shaji et al (2007), Mondal et al (2009), Vikas et al (2009), Brindha et al (2011), Dar et al (2011), Singh et al (2011), Guo et al (2012), Xu et al (2013), Jabal et al (2014), Li et al (2015) Magnesium Rao (2009) Gupta et al (1999), Farooqi et al (2007a), Xu et al (2013) Hardness Rao et al (1993), Das et al (2003) Bicarbonate Jacks et al (1993), Gupta et al (1999), Kundu et al (2001), Vasquez et al (2006), Farooqi et al (2007a), Madhnure et al (2007), Rao (2009), Keshavarzi et al (2010), Brindha et al (2011), Dar et al (2011), Singh et al (2011), Kantharaja et al (2012), Jabal et al (2014), Singh and Mukherjee (clear from the table that in general none of the parameter show good correlation EC electrical conductivity, O 18 heavy oxygen isotope Environ Chem Lett…”
mentioning
confidence: 99%
“…The positive correlations between F À with pH and with HCO 3 À indicates that at higher pH values (alkaline water nature), there is release of OH À and increase of alkalinity, where the study area have an intermediate pH and the HCO 3 À ions are the dominant species for the alkalinity. Thus, it is the higher alkalinity (HCO 3 À ) of the groundwater favor the leaching and dissolution of F À from its bearing mineral resulting in its high concentration (Kantharaja et al, 2012;Tiwari et al, 2008;Subba Rao, 2003). This relatively significant positive correlation between F À with pH may be due to the fact that there is an ion exchange between F À and OH À , commonly substitute for one another in the crystal structure of minerals owing to the similarity of their ionic radius (0.136 nm) (Sreedevi et al, 2006).…”
Section: Mutual Relationship Between Fluoride and Other Ionsmentioning
confidence: 99%
“…But in the study area it might be the substitution of OH À in the crystal structure resulting in releasing of F À into the water. Hence, higher the pH, higher will be the displacement of F À from the crystal of fluoride bearing mineral (Kantharaja et al, 2012;Srinivasamoorthy et al, 2012;Dar et al, 2011;Kumaresana et al, 2011;Jacks et al, 2005).…”
Section: Mutual Relationship Between Fluoride and Other Ionsmentioning
confidence: 99%